Learning from “The East”: Mark Tobey’s “White Writing” and the Shaping of American Abstract Expressionism - Zhong, Phyllis (Venezia Arti)
This paper explores the theme of artistic “cross-pollination” through the lens of Mark Tobey (1890-1976)’s engagement with East Asian aesthetics and philosophies, significantly impacting post-World War II American abstract art. Tobey’s integration of Chinese calligraphy and Japanese Zen Buddhism into his artistic vocabulary represents a vivid example of cultural hybridization, where Chinese and Japanese influences not only transformed his stylistic approach but also contributed to the evolution of modernist expressions in “the West”.Mark Tobey, an influential figure in American abstract art, drew profound inspiration from his experiences in China and Japan and his mentorship under the Chinese artist Teng Baiye (1900-1980), leading to the development of his unique “White Writing” style.